Comparative Morphological Studies of the Stifle Menisci in Donkeys, Goats and Dogs - Abumandour, Mohamed M.A.; Bassuoni, Naglaa Fathi; El-Gendy, Samir; Karkoura, Ashraf; El-Bakary, Raafat (Journal of Morphological Sciences, 2019)
The present work aims to provide more anatomical information on the stifle joint of the investigated species using computed tomography with gross anatomical cross-sections. The current work analyzed the stifle joint of the pelvic limbs of 12 adult donkeys, goats and dogs of both genders. The medial condyle of the femur was larger than the lateral one in the donkey, while it was smaller and lower than the lateral one in the goat and in the dog. The unsuitable femoral and tibial condyles were adapted by the presence of menisci. In the donkey, the medial meniscus was crescentic in shape, but it was semicircular in the goat, while in the dog, the medial and lateral menisci were C-shaped. In the donkey, the medial meniscus was larger than the lateral one, but in the goat and in the dog, the lateral meniscus was the largest, and more concave and thicker. The lateral meniscus was semicircular in the donkey, but it was shaped like an elongated kidney in the goat. In the goat and in the dog, the central border of two menisci was thin, concave and notched centrally. The meniscal ligaments included cranial and caudal ligaments of the medial and lateral menisci, and meniscofemoral ligament of the lateral meniscus. In the dog, the cranial ligament of the medial meniscus was absent, and the medial meniscus had no bony attachment to the tibia but it attached to the transverse intermeniscal ligament, which connected the cranial horn of the medial meniscus with the cranial ligament of the lateral meniscus. The meniscofemoral ligament connected the caudal pole of the lateral meniscus with the intercondyloid fossa of the femur.
Keywords: stifle joint; meniscal ligaments; computed tomography; anatomical sections